2012
DOI: 10.1093/pcp/pcs048
|View full text |Cite
|
Sign up to set email alerts
|

C- and D-class MADS-Box Genes from Phalaenopsis equestris (Orchidaceae) Display Functions in Gynostemium and Ovule Development

Abstract: Gynostemium and ovule development in orchid are unique developmental processes in the plant kingdom. Characterization of C- and D-class MADS-box genes could help reveal the molecular mechanisms underlying gynostemium and ovule development in orchids. In this study, we isolated and characterized a C- and a D-class gene, PeMADS1 and PeMADS7, respectively, from Phalaenopsis equestris. These two genes showed parallel spatial and temporal expression profiles, which suggests their cooperation in gynostemium and ovul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
51
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 63 publications
6
51
1
1
Order By: Relevance
“…5). We neither detected any signal of CsAG1 in the floral meristem, nor in the early flower developmental stages, different from the expression of an Orchid AG2 sub-clade member PeMADS1 in Phalaenopsis equestris , which is abundant in the whole floral meristem 26 . Future work using in situ hybridization assays will allow a precise examination of the expression patterns of different AG -like factors, leading to a better understanding under subfunctionalization among these different paralogues.…”
Section: Discussioncontrasting
confidence: 73%
See 2 more Smart Citations
“…5). We neither detected any signal of CsAG1 in the floral meristem, nor in the early flower developmental stages, different from the expression of an Orchid AG2 sub-clade member PeMADS1 in Phalaenopsis equestris , which is abundant in the whole floral meristem 26 . Future work using in situ hybridization assays will allow a precise examination of the expression patterns of different AG -like factors, leading to a better understanding under subfunctionalization among these different paralogues.…”
Section: Discussioncontrasting
confidence: 73%
“…Several AG lineage factors have been isolated from Orchidaceae species 2126 . In Dendrobium crumenatum , the putative C function gene DcOAG1 is highly expressed in all the floral organs, which leads to ap2 -like phenotypes when ectopically expressed in Arabidopsis 23 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5). The early flowering phenotypes of 35S::TrimAG transgenic Arabidopsis plants are similar to those observed in transgenic plants that ectopically express AGAMOUS ortholog genes (Tzeng et al, 2002;Benedito et al, 2004;Chiang et al, 2009;Hsu et al, 2010;Deng et al, 2011;Chen et al, 2012). These results support the prediction that C-class functional genes should have similar effects on floral induction when ectopically expressed in Arabidopsis (Tzeng et al, 2002), and confirm that TrimAG from T. macranthopsis belongs to the C-class genes.…”
Section: Discussionsupporting
confidence: 73%
“…2). TrimAG contains a MADS domain, a K-domain, and the C-terminal; the presence of these specific conserved motifs in the TrimAG protein confirmed that TrimAG is an AG ortholog (Rosin et al, 2003;Benedito et al, 2004;Tani et al, 2009;Chen et al, 2012;Delgado Sandoval et al, 2012;Waters et al, 2013).…”
Section: Agamous Ortholog Gene Isolation and Expression In Wild-type mentioning
confidence: 89%